Effect of piper extract mouthwash as postprocedural rinse on levels of Porphyromonas gingivalis in periodontitis patients - Gopalakrishnan Sundaram; Ramakrishnan Theagarajan; Gomathi Dhakshina Murthy; Gopalakrishnan Kanimozhi (Wolters Kluwer Medknow Publications, 2021)
Background: Dental biofilm plays a crucial role in periodontal disease development. Mouth rinse is used to enhance oral hygiene after scaling and root planning (SRP). The aim of the study was to evaluate the clinical and microbiological effectiveness of a piper extract mouthwash against Chlorhexidine (CHX) in periodontitis patients. Materials and Methods: Sixty patients with Stage II periodontitis participated in this study and were randomly divided into two groups (Group I - Stage II Grade A periodontitis patients were provided with prepared piper extract mouthwash and Group II - Stage II Grade A periodontitis patients were provided with 0.2% CHX). Plaque index, gingival index, sulcus bleeding index, probing pocket depth, and clinical attachment level were recorded at baseline and 30 days after SRP. Subgingival plaque samples were taken for microbial examination (colony-forming unit), quantification of Porphyromonas gingivalis using the real-time polymerase chain reaction at baseline, and 30 days after SRP. Results: Intragroup comparison for the clinical parameters showed statistically significant reduction in both the groups (P < 0.0001). Intergroup comparison for clinical parameters, there was no statistical significance seen after 30 days. Intragroup comparison for microbial analysis showed significant reduction in both the groups after 30 days (P < 0.0001). On intergroup comparison for microbial analysis, both the groups showed reduction after 30 days without significance. Conclusion: Piper extract mouthwash (Group I) showed similar antimicrobial activity against P. gingivalis when compared to 0.2% CHX mouthwash (Group II) that could be used as a substitute to CHX.